Executive functions and mathematical notions in five-year-old preschoolers - Chavarría Velásquez, Silvia Dalila (2019)
The purpose of this study is to determine the correlation between executive functions and mathematical notions in five-year-old children. In order to carry out the investigation, 80 infants of a public institution were taken as a sample, who were evaluated the different notions such as object, space, time and order; in conjunction with executive functions working memory, inhibitory control and cognitive flexibility. For which two observation sheets were used. The methodology used corresponds to a quantitative approach of basic type, basic type, correlational level, non-experimental design, cross-section. As a result, Rho = 0.638, were obtained, which indicates that the correlation is positive moderate according to Spearman with an equivalent degree of bilateral significance ap = 0.00 (p <.005), so a significant relationship between the two is affirmed. themes. It was concluded that there is a relationship between variables and dimensions.